In order to complete the square you have to consider that the third term of a perfect square should equal (b/2)^2 >> that is the the square of half the value of b, where b is the coeffiecient of the second term. So, (b/2)^2 = (16/2)^2 = (8)^2 = 64 The perfect match for the third term is 64 x2 + 16x = 3 You have to add 64 on both sides of the equation just to maintain equality, x2 + 16x + 64= 3 + 64 x2 + 16x + 64 = 67 ( x + 8)^2 = 67 Then it is easier to factorize and find values of x, take the square root from both sides, (x + 8) = sqrt(67) sqrt(67) = 8.18 1) x = 8.18 - 8 = 0.18 2) x = -8.18 - 8 = -16.18